The Rhyme of Joyful Feeling in “To Autumn” By John Keats - Marpaung, Marlin Steffi; ., Rahmadhan (Acuity: Journal of English Language Pedagogy, Literature and Culture, 2021)
Rhyme is one of the important elements in the poem. The function of rhyme is to attract the readers’ attention. This study focuses on the rhyme of joyful feeling in the poem “To Autumn” written by John Keats. The objectives of this study are to determine the types of joyful rhyme reflected in John Keats’ poem “To Autumn” and to interpret how the rhyme reflected the joyful feeling in the poem. The Semiotic Theory by Charles Sanders Peirce was used in this study. The methodology used is descriptive qualitative research and a triangulation strategy was used in this study as well as the using of data from library research to present a descriptive issue. The result of this study showed that there are twelve perfect rhymes, eight eye rhymes, and four light rhymes from the “To Autumn” poem and there are twenty words were used to interpret the using of icons, symbols and index based on Charles Sanders Peirce theory.